Asuhan Keperawatan Pada Ny.D dengan Diagnosis PS Resection + Susp. Pneumonia + Efusi pleura PI Dextra-Alkalosis respiratorik - Helpvina Sianipar; Mula Tarigan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Background: Pneumonia, pleural effusion, and respiratory alkalosis are complex conditions that are often found in patients after surgical resection (PS Resection). These conditions can compromise respiratory function and increase the risk of serious complications, such as respiratory failure and death. Evidence-based maintenance approaches, including non-pharmacologic pursed-lipbreathing (PLB) therapy, have been shown to be effective in managing respiratory distress. Objectives: This study aimed to apply the application of PLB therapy in patients with these conditions. Methods: This study is a case study on a 23-year-old female patient at Adam Malik General Hospital. The patient had a history of PS Resection, susp. pneumonia, dextra pleural effusion, and respiratory alkalosis. OTB intervention was performed four times a day for three consecutive days. Data were collected through measurement of oxygen saturation and level of breathlessness before and after the intervention. Results: The results showed that OTB therapy was effective in increasing oxygen saturation and decreasing the patient's shortness of breath level. The patient's breathlessness level decreased from scale 7 (severe) to scale 1 (mild) within three days. The intervention worked by improving gas exchange and increasing respiratory ventilation efficiency. In addition, PLB provides additional benefits in the form of relaxation and increased activity tolerance. Conclusion: The conclusion of this study is that PLB therapy is a non-pharmacological method that is simple, effective, and can be applied to patients with complex respiratory disorders. This therapy can also teach patients and families to support home care. Further studies with larger samples and longer observation periods are needed to confirm these findings.